(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
"While smartphone integration in technical colleges acts as a powerful catalyst for equitable information access and interactive diagnostics, it simultaneously triggers cognitive fragmentation and the erosion of deep-focus capabilities. This paper argues that technical education must move beyond the ’prohibition versus permission’ binary toward a Dynamic Integration model, rebranding cellular devices as professional instruments rather than personal distractions to ensure students master the machine rather than be mastered by it."